Phenotypic and genotypic antimicrobial susceptibility patterns of the emerging human respiratory pathogen Mycoplasma amphoriforme isolated from the UK and Denmark. (1st September 2022) - Day, Jessica; Afshar, Baharak; Rowlands, Richard S; Umer, Taiba S; Windsor, Helena; Paukner, Susanne; Jensen, Jorgen S; Spiller, Owen B; Chalker, Victoria J; Beeton, Michael L; ,
Abstract: Objectives: To determine the phenotypic and genotypic antibiotic susceptibility of Mycoplasma amphoriforme isolates recovered from patients in the UK and Denmark. Methods: Seven isolates of M. amphoriforme were examined for antimicrobial susceptibility to seven antibiotics using the microbroth dilution assay in line with the CLSI guidelines for mycoplasmas. Each isolate was additionally subjected to WGS to identify resistance-associated mutations. Based on the consensus sequences from the genomic data, PCR primers were designed, and tested, for the amplification of the QRDR within the parC gene. Results: Of the seven isolates investigated, four (57%) were resistant to moxifloxacin (0.5–1 mg/L) and levofloxacin (1–2 mg/L), compared with those that were susceptible (0.03–0.06 and 0.006 mg/L, respectively). Isolate H29 was resistant to five of the seven antibiotics tested: moxifloxacin, 0.5 mg/L; levofloxacin, 2 mg/L; azithromycin, 64 mg/L; erythromycin, 128 mg/L; and clindamycin, 64 mg/L. All isolates were susceptible to tetracycline (0.06 mg/L) and lefamulin (0.001–0.004 mg/L). Mutations from genomic data confirmed the presence of an S89F mutation within the ParC protein among all fluoroquinolone-resistant isolates and an A2059G mutation in the 23S rRNA gene in the macrolide- and lincosamide-resistant isolate H29. Conclusions: To the best of our knowledge, this is the first time where phenotypic and genotypic resistance data have been paired for M. amphoriforme confirming a correlation between the two. These data suggest the need for focused testing and resistance determination of isolates from high-risk patients given the backdrop of a high prevalence of antimicrobial resistance.